REPRESENTASI PENDIDIKAN MASYARAKAT TERPENCIL DALAM FILM SOKOLA RIMBA KARYA MIRA LESMANA - Reni Damayanti; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Sokola Rimba is a film full of education and humanity. This film reveals the life story of a teacher who devotes himself to fellow humans, especially the jungle people. Education is a process with certain methods so that someone acquires knowledge, understanding and the way people behave according to their needs. This study aims to provide knowledge to the people who live in remote areas, especially the suku rimba, on the importance of education so that there is no more land transfer and to know the denotation, connotation and myths of education in remote communities in the Sokola Rimba film.This study uses descriptive qualitative research methods, using Roland Barthes's semiotic method which includes denotations, connotations and myths. the subject of this research is the scenes that identify education itself in the film Sokola Rimba. While the object of this research is the Sokola Rimba film. Data collection techniques used are observation, documentation and literature. In achieving the validity of the data in this study, the authors used triangulation.The results of the study show that: (1) The meaning of denotation in the film sokolah rimba is how the actual state of education is in the jungle tribe that is in the learning process only by using tools that have natural surroundings such as rubber seeds. (2) The meaning of connotation is generally the education factor in remote communities is education carried out in the open or open world, not using buildings either semi or permanent. (3) The myth in the film sokolah rimba is seen from several perceptions that have been embedded that the people who live in remote areas is an innocent, primitive, and illiterate society.Keywords: Film, Semiotics, Education, and Sokola Rimba